Perspectives of Management in the Time of Knowledge Economy and Information Society - Vološin, Martin; Vološinová, Darina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The paper is focused on current issues of corporate governance and management in the era of transition to a knowledge economy and information society. The first part discusses basic factors of economic transformation and restructuring of the economy on the way to a modern post-industrial society. The second part of the article is dedicated to measuring the degree of knowledge economy development and problems of management of economic subjects, with a focus on increasing the competitiveness of Slovakia at the current stage of globalization and transformation of the economy.

Artykuł koncentruje się na bieżących kwestiach zarządzania korporacyjnego w dobie przejścia do gospodarki wiedzy i społeczeństwa informacyjnego. Pierwsza część omawia podstawowe czynniki transformacji gospodarczej i restrukturyzacji gospodarki w drodze do nowoczesnego społeczeństwa postindustrialnego. Druga część artykułu poświęcona jest pomiarowi stopnia rozwoju gospodarki opartej na wiedzy i problemom zarządzania podmiotami gospodarczymi, ze szczególnym naciskiem na zwiększenie konkurencyjności Słowacji na obecnym etapie globalizacji i transformacji gospodarki.
Keywords: knowledge economy; information society; structural changes; management; corporate governance; Gospodarka oparta na wiedzy; społeczeństwo informacyjne; zmiany strukturalne; zarządzanie; nadzór korporacyjny